PENGGUNAAN MEDIA BATANG NAPIER DALAM MENINGKATKAN KEMAMPUAN OPERASI PERKALIAN BAGI ANAK KESULITAN BELAJAR KELAS 3 SD 11 BELAKANG TANGSI PADANG - Novi - Aristiani (Universitas Negeri Padang, 2013)
Research background by problems that researchers in the field discovered that a child's learning difficulties in 3rd grade 11 Rear Padang barracks that had difficulty in multiplication of numbers., children experience difficulties on a number of questions given and the child has not been able to answer correctly. Researchers therefore be helped to improve their child's learning difficulties in multiplication of numbers through media napier rods. The research methodology used is a single-subject research (SSR) dengandesain adala AB, which compares the number multiplication skills learning disabilities in children baseline condition and treatment condition in the form of Visual Analysis Of Charts. Results of this study are shown in the analysis of data and analysis of the condition among the conditions that indicate a change in the ability of the multiplication of numbers in the child toward a better estimate of the trend is evidenced by the positive direction (+), trace data increases and thus the hypothesis is accepted, it means the media stems napier and can significantly improve the ability of the multiplication of numbers in children difficult belajarkelas 3. Suggested for classroom teachers in order to use the Trunk Media Napier to teach multiplication in numbers.